A Gene Implicated in Activation of Retinoic Acid Receptor Targets Is a Novel Renal Agenesis Gene in Humans. Issue 1 (26th July 2017) - Brophy, Patrick D; Rasmussen, Maria; Parida, Mrutyunjaya; Bonde, Greg; Darbro, Benjamin W; Hong, Xiaojing; Clarke, Jason C; Peterson, Kevin A; Denegre, James; Schneider, Michael; Sussman, Caroline R; Sunde, Lone; et al.
Abstract: Renal agenesis is a devastating birth defect, and although genes encoding retinoic acid signaling components have been shown to be important for renal... Renal agenesis (RA) is one of the more extreme examples of congenital anomalies of the kidney and urinary tract (CAKUT). Bilateral renal agenesis is almost invariably fatal at birth, and unilateral renal agenesis can lead to future health issues including end-stage renal disease. Genetic investigations have identified several gene variants that cause RA, including EYA1, LHX1, and WT1 . However, whereas compound null mutations of genes encoding α and γ retinoic acid receptors (RARs) cause RA in mice, to date there have been no reports of variants in RAR genes causing RA in humans. In this study, we carried out whole exome sequence analysis of two families showing inheritance of an RA phenotype, and in both identified a single candidate gene, GREB1L . Analysis of a zebrafish greb1l loss-of-function mutant revealed defects in the pronephric kidney just prior to death, and F0 CRISPR/Cas9 mutagenesis of Greb1l in the mouse revealed kidney agenesis phenotypes, implicating Greb1l in this disorder. GREB1L resides in a chromatin complex with RAR members, and our data implicate GREB1L as a coactivator for RARs. This study is the first to associate a component of the RAR pathway with renal agenesis in humans.